Photophysical and Photoelectrochemical Properties of CsPbBr3 Films Grown by Electrochemically Assisted Deposition. Issue 19 (27th July 2022) - Gau, Daniel L.; Ramírez, Daniel; Iikawa, Fernando; Riveros, Gonzalo; Díaz, Patricia; Verdugo, Javier; Núñez, Gerard; Lizama, Susy; Lazo, Pamela; Dalchiele, Enrique A.; Contreras, Lidia; Idigoras, Jesús; et al.
Abstract: Perovskite have had a great impact on the solid‐state physics world in the last decade not only achieving great success in photovoltaics but, more recently, also in the implementation of other optoelectronic devices. One of the main obstacles for the adoption of Pb‐based perovskite technologies are the high amounts of Pb needed in the conventional preparation methods. Here we present for the first time a detailed analysis of the photophysical and photoelectrochemical properties of CsPbBr3 films directly grown on fluorine‐doped tin oxide (FTO) coated glass through a novel technique based in the electrodeposition of PbO2 as CsPbBr3 precursor. This technique allows to save up to 90 % of the Pb used compared to traditional methods and can be scalable compared with the commonly used spin‐coating process. The low temperature analysis of their photoluminescence spectra, performed in both steady state and time dependence, revealed a strong interaction between electrons and longitudinal optical (LO) phonons dominant at high temperatures. On the other hand, the electrochemical and photoelectrochemical analysis proves that CsPbBr3 prepared using this new method has state‐of‐the‐art features, showing a p‐type behavior under depletion regime. This is also confirmed by photoelectrochemical measurements using p‐benzoquinone as target molecule. These results prove that the proposed method can be used to produce excellent CsPbBr3 films, saving much of the lead waste. Abstract : A detailed analysis of the photophysical and photoelectrochemical properties of CsPbBr3 films electrochemically grown through a novel technique on fluorine‐doped tin oxide is presented. An analysis of the low‐temperature photoluminescence spectra reveals a strong interaction between electrons and longitudinal optical phonons. (Photo)electrochemical analysis proves that CsPbBr3 shows a p‐type and recombinative behavior close to that of state‐of‐the‐art methods to prepare CsPbBr3 .